POWER AND PRECISION: EXPLORING THE EFFICIENCY OF PLANETARY GEAR TRAINS WITH CLOSED DIFFERENTIALS - Liu, Hua Feng (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
Gears, an integral component of the manufacturing industry, serve as irreplaceable elements across diverse sectors of society. A comprehensive examination of gears holds the potential to propel China into the echelons of manufacturing prowess. In the realm of mechanical transmission, gear mechanisms, including planetary gears, occupy a prominent position, finding application in automobiles, ships, mining machinery, and beyond. Planetary gear trains, as a sophisticated variation of conventional gear transmission, offer distinct advantages, encompassing compact dimensions, intricate structures, substantial power transmission capabilities, and robust load-bearing capacities. As a result, planetary gear trains have gained widespread recognition as viable alternatives to conventional gear systems. One of the most noteworthy innovations in this field is the closed differential planetary gear system. This system is a fusion of two key components: the single degree of freedom star gear train, known as the closed stage, and the closed two-degree of freedom differential planetary gear train, known as the differential stage. This amalgamation creates the closed differential planetary transmission system. The system leverages multiple planetary gears, also referred to as star wheels, to distribute the load and facilitate power distribution. It boasts several advantages, including a compact form factor, lightweight design, and robust load-bearing capacity. This distinctive configuration is a testament to the potential for enhancing mechanical transmission systems.